Adoption of LLMs in Requirements Engineering: What Practitioners Are Worried About? - Santos, Reine; Steinmacher, Igor; Conte, Tayana; Oran, Ana Carolina; Gadelha, Bruno (Anais do Simpósio Brasileiro de Qualidade de Software (SBQS); 2025: Anais do XXIV Simpósio Brasileiro de Qualidade de Software, 2025)
Requirements engineers face persistent challenges related to stakeholder communication, information ambiguity, and the precise definition of system needs. In this context, user stories have gained traction as a structured, user-centered approach to representing requirements. At the same time, there is growing interest in using Large Language Models (LLMs) to automate such tasks. However, before proposing automated solutions, it is essential to understand how professionals currently elicit requirements, what techniques and tools they use, and how open they are to adopting LLMs for user story generation. To investigate this, an online survey was conducted with 21 software industry professionals experienced in requirements engineering. The questionnaire, divided into three sections, explored current practices in requirements elicitation and validation, as well as the use of LLMs in these activities. The results showed that 57.1% of participants currently use user stories in their work. Among them, 66.7% reported using LLMs, primarily Chat-GPT, for tasks such as brainstorming and content review. Of these LLM users, 75% also apply them to user story generation, citing benefits such as increased speed, standardization, and improved story quality. However, limitations were also identified, including lack of context, potential over-reliance, and legal concerns. These findings indicate that there is growing interest in adopting LLMs in requirements engineering, including user story generation, as long as their use aligns with established practices and is supported by effective prompting, contextual input, and data privacy safeguards.